2021
DOI: 10.1021/acschemneuro.1c00001
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid Inhibits α-Synuclein Aggregation at Multiple Stages and Reduces Its Cytotoxicity

Abstract: α-Synuclein is a natively unfolded protein and its deposition in the Lewy body and Lewy neurites in the substantia nigra region of the brain is linked to Parkinson's disease (PD). The molecular mechanisms of α-synuclein aggregation and its clearance have not been well understood. Until now, several strategies have been designed to inhibit α-synuclein aggregation and related cytotoxicity. Polyphenols, small molecules, synthetic peptides, and peptide-derived molecules have been considered as potential candidates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Yan et al have revealed the effect of EA on prion protein fibrillization . Recently, Kumar et al indicated that EA inhibits aggregation of wild-type αS at multiple stages . However, the present study aimed was to systematically assess the modulatory effect of EA against uninduced (wild-type αS) as well as mutation (A53T and E46K) and metal-induced aggregation of αS.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Yan et al have revealed the effect of EA on prion protein fibrillization . Recently, Kumar et al indicated that EA inhibits aggregation of wild-type αS at multiple stages . However, the present study aimed was to systematically assess the modulatory effect of EA against uninduced (wild-type αS) as well as mutation (A53T and E46K) and metal-induced aggregation of αS.…”
Section: Introductionmentioning
confidence: 94%
“…29 Recently, Kumar et al indicated that EA inhibits aggregation of wild-type αS at multiple stages. 30 However, the present study aimed was to systematically assess the modulatory effect of EA against uninduced (wild-type αS) as well as mutation (A53T and E46K) and metal-induced aggregation of αS. Hence, this study reveals that EA could be a potential agent against familial cases as well as sporadic cases of Parkinson's disease.…”
Section: Introductionmentioning
confidence: 97%
“…NMR spectroscopy has been successfully employed in several drug discovery campaigns for structured protein targets but has found limited success in the investigation of IDPs . There have been several NMR studies that explore small-molecule binding to mature aSyn fibrils , as well as a few reportsusing 1 H, 15 N-HSQC NMR spectroscopy (HSQC)where small molecules (including epigallocatechin gallate (EGCG), Baicalin, and dopamine (DOPA)) have been shown to engage monomeric or low-molecular-weight aSyn species. …”
Section: Introductionmentioning
confidence: 99%
“…Various peptides, 14 nanoparticles, 15 small molecules, 16 antibodies, 17 and polymers 18 blocked α-Syn aggregation, destabilized pre-existing α-Syn fibrils, and suppressed their growth. Amidst these inhibitors, small molecules originating from natural sources such as epigallocatechin gallate (EGCG), 16 b ellagic acid (EA), 19 curcumin, 20 rosmarinic acid, 21 dihydromyricetin (DHM), 22 brazilin, 23 and baicalein, 24,25 have gained special interest because of their low toxicity and high availability.…”
Section: Introductionmentioning
confidence: 99%